ANALYSIS OF THE MACRO EXPERIMENT DATA TO COMPARE PARTICLE ARRIVAL TIMES UNDER GRAN SASSO - Ronga, Francesco (Acta Polytechnica, 2013)
The claim of a neutrino velocity different from the speed of the light, made in September 2011 by the Opera experiment, suggested the study of the time delays between TeV underground muons in the Gran Sasso laboratory using the old data of the MACRO experiment, ended in 2000. This study can also give hints on new physics in the particle cascade produced by the interaction of a cosmic ray with the atmosphere.